Genetic diversity and molecular characterization of Saccharomyces cerevisiae strains from winemaking regions - Schuller, Dorit Elisabeth (2006)
Apresentação efectuada no "Congresso de Cachaça, 1, Belo Horizonte, Brazil, 2006"